The Effect of Treated Rice Milling Waste on Performance, Nutrient Retention, Carcass and Organ Characteristics of Finisher Broilers - Amaefule, K.U.; Iheukwumere, F.C.; Lawal, A.S.; Ezekwonna, A.A. (International Journal of Poultry Science, 2005)
One hundred and twenty 4-week old broilers were used to evaluate the effect of various treatment methods of rice milling waste (RMW) on growth performance, nutrient retention and organ characteristics of finisher broilers. Rice milling waste was treated with urea (D2), poultry droppings (D3) and water (D4), while untreated waste (D1) served as control. Urea treated RMW diet significantly (P< 0.05) improved body weight, weight gain and dressed weight of broilers. Organ weights, dry matter intake and nitrogen free extract were not significantly (P>0.05) influenced by the dietary treatments. Broilers fed untreated RMW diet recorded significantly higher feed intake than broilers fed other diets. The results showed that rice milling waste, when treated with urea (fertilizer grade) and included in finisher broiler diets, could enhance their performance.